Green Space Conceptual Design for the Neighbourhood of Settlements along Martapura River in Banjarmasin - Hanny Maria Caesarina (Ruang, 2020)
Banjarmasin still struggles to improve the environmental quality of the settlements in some riparian areas that built directly above Martapura river. The settlements are densely populated with limited pathways without any open space. The local government implemented waterfront development to improve the environmental quality, such as a green village concept by installing some greeneries along the settlements to create a greener neighbourhood. The main problem was there were no available land for greenspace. The aim of this research was to design a conceptual design for green space along the river based on the evaluation of the existing condition after the green village concept already implemented. Series of field observations, interviews, and literature review was done to get an actual condition of the study area. The data analyzed with a descriptive-qualitative approach and resulted that the quality of the green space in the neighbourhood can be improved with a special green space design for the limited space. We produce a conceptual design that fulfil the criteria of green space for settlements along the Martapura river which are vertical garden, floating communal space and floating garden These concepts may suitable for green space in limited space and connected with the river as blue space